Electron microscopy of hepatitis B virus components in chronic active liver disease. Issue 6 (June 1979) - De Vos, R; Ray, M B; Desmet, V J
Abstract : Eighteen liver biopsy specimens from patients with hepatitis B surface antigen (HBsAg) positive chronic aggressive hepatitis were studied by electron microscopy. All cases were selected on the basis of positive liver cell membrane fluorescence for HBsAg on immunohistochemical investigation. Striking changes in the morphology of the liver cell membrane were observed in nearly all cases. Furthermore, a dual aspect of hepatitis B core antigen (HBcAg) is described. HBcAg particles may occur as either 'naked' or 'cloudy' particles surrounded by semi electron dense material. The nature of the 'cloud' remains to be identified.